Flow resistance in straight gravel bed inbank flow with analytical solution for velocity and boundary shear distribution. Issue 1 (2nd January 2021) - Singh, Prateek Kumar; Khatua, Kishanjit Kumar; Banerjee, Sumit
ABSTRACT: In the present investigation, the roughness characteristics of the gravel bed is tested and modelled for the no-load condition. A straight trapezoidal channel having gravel bed surface of grain size D50 as 13.5 mm for no-load condition is used to carry out the investigation. Depth averaged velocity (DAV) and boundary shear stress (BSS) have been measured for five different depths. An improved model for prediction of friction factor is derived as the function of corresponding hydraulic radius and average diameter of the gravel. This improved model is validated with the models of past investigators. Furthermore, BSS is then calculated using Shiono and Knight Method (SKM), which is dependent on the following hydraulic parameters, such as friction factor f, coefficient of eddy viscosity λ and secondary flow term Г . Since friction factor is modelled for the given channel, same model is used to calculate the value of f over the bed, which tests the reliability of the model while using numerical method. The lateral distribution of DAV and BSS is shown for five different flow depths, which elaborate the bed friction due to the no-load condition. Finally, friction factor model is corroborated on two reaches of the natural river.